Determining the heat flow through the cabinet walls of household refrigerating appliances - Paul, Andreas; Baumhögger, Elmar; Elsner, Andreas; Moczarski, Lukas; Reineke, Michael; Sonnenrein, Gerrit; Hueppe, Christian; Stamminger, Rainer; Hoelscher, Heike; Wagner, Hendrik; Gries, Ulrich; Freiberger, Alfred; et al. (International Journal of Refrigeration)
The increase of the thermal conductivity of PUR foam in the insulation of the cabinet is an important cause for aging processes of household refrigerating appliances. To determine the influence of the PUR foam aging on energy consumption, the development of a new measurement method is necessary be- cause current methods influence the aging behavior of household refrigerators and are therefore not applicable in general. Based on a latent heat sink, constructed as an ice water bucket, a new measure- ment method is developed to determine the k ·A value over time. With this method, the k ·A value of four household refrigerating appliances was determined over an interval of 14 months. The k ·A value increased between 3.6% and 11.5% during this period.

Improving the performance of household refrigerating appliances through the integration of phase change materials in the context of the new global refrigerator standard IEC 62552:2015 - Sonnenrein, G.; Baumhögger, Elmar; Elsner, A.; Morbach, A.; Neukötter, M.; Paul, A.; Vrabec, J. (International Journal of Refrigeration)

Improving the performance of household refrigerating appliances through the integration of phase change materials in the context of the new global refrigerator standard IEC 62552:2015 - Sonnenrein, Gerrit; Baumhögger, Elmar; Elsner, Andreas; Morbach, A.; Neukötter, Moritz; Paul, Andreas; Vrabec, J. (International Journal of Refrigeration)
The influence of latent heat storage elements on the cooling performance and the temperature rise time of household refrigerating appliances is studied experimentally in the context of the “new global refriger- ator standard”IEC 62552:2015. In addition to the daily energy consumption, this international standard- ization introduced performance tests for cooling capacity and temperature rise time. While the cooling capacity has long been anchored in various test procedures of consumer organizations, the temperature rise time, which has only been tested on freezers so far, will be a decisive factor in the future. Moreover, the need for so-called "smart appliances" that may balance power consumption is increasing since such devices may compensate the volatility of renewable energies and thus stabilize the power grid. Against this background, eight commercial household refrigerators and refrigerator-freezers are equipped with polymer-bound phase change materials (PCM) and their performance is determined under the new stan- dard test conditions. The results show that the introduction of PCM increases the cooling capacity by up to 33 % and also increases the temperature rise time by up to 145 %, without affecting power consump- tion, as compared to the unmodified refrigeration appliances.

Copolymer-bound phase change materials for household refrigerating appliances: experimental investigation of power consumption, temperature distribution and demand side management potential - Sonnenrein, G.; Baumhögger, Elmar; Elsner, A.; Fieback, K.; Morbach, A.; Paul, A.; Vrabec, J. (International Journal of Refrigeration)

Copolymer-bound phase change materials for household refrigerating appliances: experimental investigation of power consumption, temperature distribution and demand side management potential - Sonnenrein, Gerrit; Baumhögger, Elmar; Elsner, Andreas; Fieback, K.; Morbach, A.; Paul, Andreas; Vrabec, J. (International Journal of Refrigeration)
This study presents the results of an experimental investigation of the influence of latent thermal heat storage elements on the power consumption as well as the temperature distribution of commercial household refrigerators.Two evaporator types and a standard wireand- tube condenser are equipped with copolymer-bound phase change materials (PCM) and the performance is determined under standard conditions. The results show that refrigerating appliances equipped with PCM can be optimized through modifications of the control strategy to achieve different targets: (a) Power consumption can be significantly reduced by increasing the evaporator and decreasing the condenser temperature. (b) Temperature fluctuations in the refrigerator’s fresh-food compartment during the cooling cycle can be reduced from 4 °C to 0.5 °C. (c) The cooling cycle duration can be tripled without compromising the fresh-food compartment conditions. The latter may help to meet the growing demand for balancing power consumption to stabilize the power grid, e.g. if the share of highly fluctuating, sustainable energy supply is large.

Reducing the power consumption of household refrigerators through the integration of latent heat storage elements in wire-and-tube condensers - Sonnenrein, G.; Elsner, A.; Baumhögger, Elmar; Morbach, A.; Fieback, K.; Vrabec, J. (International Journal of Refrigeration)

Prediction methods for pool boiling heat transfer: A state-of-the-art review - Gorenflo, Dieter; Baumhögger, Elmar; Herres, Gerhard; Kotthoff, Stephan (International Journal of Refrigeration)

Nucleate pool boiling, film boiling and single-phase free convection at pressures up to the critical state. Part II: Circumferential variation of the wall superheat for a horizontal 25mm copper cylinder - Gorenflo, Dieter; Baumhögger, Elmar; Windmann, Thorsten; Herres, Gerhard (International Journal of Refrigeration)

Nucleate pool boiling, film boiling and single-phase free convection at pressures up to the critical state. Part I: Integral heat transfer for horizontal copper cylinders - Gorenflo, Dieter; Baumhögger, Elmar; Windmann, Thorsten; Herres, Gerhard (International Journal of Refrigeration)